Truancy and Job Satisfaction Towards Sponsored Child - Care Facility in India - Agrawal, Pooja; Gautam, Omvir (Prabandhan: Indian Journal of Management, 2018)
The major issue is child-care in the present scenario for dual career couples. The present paper attempted to identify the need of employers' sponsored child-care facilities. Moreover, it analyzed the impact of sponsored child care facility on the truancy rate and level of job satisfaction of the employees. For this purpose, a cross-sectional study was conducted from January - June 2017. A close - ended questionnaire was self-administered to dual career couples from Haryana, Punjab, and Uttar Pradesh to analyze their perceptions towards employers' sponsored child-care facilities ; 320 questionnaires were distributed in the selected sampling region and only 205 were returned, with a response rate of 64.04%. Structural equation modeling was employed for the analysis purposes. Results indicated that there was a higher need of employers' sponsored child-care facility. These facilities had a significant impact on the truancy rate of employees. Future studies can evaluate how employers and employees get benefited by this child-care facility. The present study revealed the value of employers' sponsored child-care facilities.